IMPLEMENTASI PSAK 16 PADA ENTITAS PERBANKAN BUMN - Simorangkir, Panubut (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
Fixed assets are certainly instrumental to the activities of a company, for servicecompanies, for trading companies, as well as industrial companies. Value on fixed assets is not small. Therefore, it affects the company both in the statement of financial position and profit and loss of the company. The cost on a fixed asset will decrease due to the usage of the property, plant and equipment. The provisions governing property, plant and equipment are listed in PSAK 16 (convergence with IAS 16). The results of this research and analysis that have been done in this research, it can be concluded that the implementation of PSAK 16 in state owned enterprises (BUMN) banking industry industry for the year 2014-2015 can be done smoothly although there are difficulties in the stages to ensure the occurrence of impairment and market pricing. In general, all BUMN entities have applied PSAK 16 in accordance with the appropriate.